ISU-ISU KRISIS DALAM NOVEL-NOVEL DYSTOPIAN SCIENCE FICTION AMERIKA - Muajiz Muallim (POETIKA, 2017)
This paper focuses on issues and discourses about the crisis that existed in the dystopian science fiction (dystopian sf) novels. In this case, Hunger Games Trilogy (2008-2010), Maze Runner Trilogy (2009-2011), Divergent Trilogy (2011-2013) are the main object to see how far the text of dystopian sf novels address issues and discourses about the crisis within. Dystopian sf novels that are the counter-discourse of utopian sf novels has no longer present the utopian elements of the future, but, contrastly present the worst possibilities of the future. It appears that the dystopian sf writers present narratives about crisis, poverty, darkness, and pessimism in their novels. It even reads as a form of criticism and warning that the writers are trying to convey to the reader through fictional texts. In the end, the conditions of crisis seen in the text of these dystopian sf novels open its relationship with the world's history outside the text.Keywords: crisis, dystopian science fiction, America, history.